Dialektika Ilmu Dan Agama: Model, Contoh Dan Tokoh - Adni, Puji Roudlotul Adni (Dahzain Nur, 2025)
The relationship between science and religion has long been a subject of continuous debate, as the two are often viewed as standing on different foundations and pursuing different kinds of truth. This article examines the historical and conceptual dynamics of that relationship by tracing key debates, representative models, and influential thinkers who have shaped the discourse. Using a literature-based descriptive method, the study highlights how differences in ontological, epistemological, and axiological perspectives frequently spark tensions between scientific findings and religious teachings. These tensions can be seen, for instance, in the dispute over heliocentrism involving Galileo or the controversy surrounding Darwin’s theory of evolution. Ian G. Barbour’s four models conflict, independence, dialogue, and integration serve as the analytical framework for understanding these interactions. The conflict model captures moments of open confrontation, while the independence model treats science and religion as addressing distinct domains. The dialogue model offers space for constructive engagement, and the integration model seeks a more unified framework through approaches such as natural theology, theology of nature, and systematic synthesis. The study concludes that the relationship between science and religion is neither static nor binary; instead, it evolves in line with historical developments and the contributions of various thinkers. Consequently, both domains hold the potential to complement one another in enriching human understanding of life and the universe.